Artificial stone plate and preparation method thereof
The artificial stone plate formulation and preparation method improve surface texture and glossiness by incorporating mica flakes and a transparent protective layer, resulting in a vibrant, decorative stone surface.
Patent Information
- Application Number
- CN202411270511.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
Existing resin-based artificial stone surfaces lack natural texture and luster, appearing mechanical, dull, and gray, with limited decorative appeal.
An artificial stone plate formulation comprising unsaturated polyester resin liquids A and B, mica flakes, and fillers, along with a preparation method involving a transparent protective layer and resin coating, enhances surface texture and glossiness.
The artificial stone plate achieves a clear, natural mica flake texture with strong pearl-like luster and vibrant color effects, providing a distinct decorative appearance.
Smart Images

Figure CN119118568A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to an artificial stone plate and a preparation method thereof. Background Art
[0002] Artificial stone is an important component of modern building decoration materials. It can make up for the shortcomings of natural stone in terms of resources, environmental protection, construction, etc., and can replace natural stone with a variety of appearances. Artificial stone mainly includes resin-based artificial stone, composite artificial stone, cement-based artificial stone, and sintered artificial stone.
[0003] Among them, resin-based artificial stone is a kind of stone made of unsaturated polyester resin or epoxy resin as a binder, natural marble or inorganic powders such as calcite, dolomite, silica sand, glass powder, and appropriate amount of flame retardant, color, etc., which is formed and solidified by mixing ingredients, spreading, vibration compression, extrusion, etc. It can be used in the decoration of family houses, hotels, restaurants, bars, shopping malls, hospitals, etc., and is a large-volume artificial stone in interior decoration projects.
[0004] The existing resin-based artificial stone uses molds or spraying techniques to create various texture effects on the surface, such as terrazzo texture, original stone block, antique stone and other textures, and can even produce textures with natural marble, granite, slate and other textures. However, the surface texture of the existing resin-based artificial stone is mechanical and dull, the texture is stiff and astringent, and the luster is dull and gray. Summary of the invention
[0005] The object of the present invention is to provide an artificial stone plate with clear texture and good glossiness.
[0006] Another object of the present invention is to provide a method for preparing an artificial stone slab, which is simple and efficient.
[0007] The present invention solves the technical problem by adopting the following technical solutions.
[0008] On the one hand, an embodiment of the present invention provides an artificial stone plate, which comprises the following raw materials, calculated by mass percentage:
[0009] Unsaturated polyester resin liquid A 5-20%, unsaturated polyester resin liquid B 10-30%, mica flakes 1-40% and filler 20-60%;
[0010] The unsaturated polyester resin liquid A comprises the following raw materials by weight: 100 parts of unsaturated polyester resin, 0.1-2 parts of curing agent, 0.1-2 parts of accelerator, 0.1-2 parts of coupling agent, and 0.1-2 parts of inhibitor;
[0011] The unsaturated polyester resin liquid B comprises the following raw materials by weight: 100 parts of unsaturated polyester resin, 0.1-2 parts of curing agent, 0.1-2 parts of accelerator, 0.1-2 parts of coupling agent, 0.1-2 parts of inhibitor; and 0.01-1 parts of color concentrate.
[0012] In some embodiments of the present invention, the filler is glass sand or quartz sand, and the particle size of the filler is 0.061-30 mm.
[0013] In some embodiments of the present invention, the curing agent is one of methyl ethyl ketone peroxide, cyclohexanone peroxide, methyl isobutyl ketone peroxide, benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, 2,4-dichlorobenzoyl peroxide and dodecyl peroxide.
[0014] In some embodiments of the present invention, the promoter is one of cobalt naphthenate, vanadium naphthenate, cobalt isooctanoate, vanadium isooctanoate and N,N-dimethylaniline.
[0015] In some embodiments of the present invention, the polymerization inhibitor is one of stearic acid, epoxy resin and dioctyl phthalate.
[0016] In some embodiments of the present invention, the coupling agent is a silane coupling agent or a titanate coupling agent.
[0017] On the other hand, an embodiment of the present invention provides a method for preparing an artificial stone plate, comprising the following steps: S1, stirring an unsaturated polyester resin liquid A uniformly, pouring it into a mold, and curing it to form a transparent protective layer;
[0018] S2, mixing the unsaturated polyester resin liquid B and the mica flakes, stirring evenly, pouring into a mold, and flattening and compacting;
[0019] S3, pouring the filler into the mold, vibrating and pressing under vacuum, solidifying and forming, cooling, and obtaining a stone blank;
[0020] S4, a scraping machine scrapes and levels the stone blank;
[0021] S5, coating a resin layer on the surface of the transparent protective layer of the stone blank, curing, and polishing to obtain the artificial stone plate.
[0022] In some embodiments of the present invention, in step S1, the transparent layer has a thickness of 1-5 mm.
[0023] In some embodiments of the present invention, in step S5, the thickness of the resin layer is 1-3 mm.
[0024] In some embodiments of the present invention, in step S5, the raw material of the resin layer is one of unsaturated polyester resin, epoxy resin and UV resin.
[0025] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:
[0026] The artificial stone plate of the present invention has natural mica flakes added to the raw materials. The cleavage surface of the mica has a pearl or semi-metallic luster. Through multiple reflections and interference of light, a good pearl effect, color effect and perspective flash color effect can be produced on the surface of the stone. A strong pearl-like luster is produced from multiple levels at all angles. The surface of the stone plate has a different texture, luster and texture from other artificial stone plates, and has a brand-new decorative effect.
[0027] The preparation method provided by the present invention first uses unsaturated polyester resin liquid to form a transparent protective layer, which can be used to wrap the mica sheets in the raw material to prevent water from entering between the layered structures of the mica sheets during the subsequent flattening and thickness determination; then, the unsaturated polyester resin liquid and the mica sheets are added to the mold, and the unsaturated polyester resin liquid is used to fully wet the mica sheets, so as to prevent the mica sheets from being delaminated and peeled off in the later stage. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 This is a physical picture of a stone slab prepared in Example 1 of the present invention;
[0030] Figure 2 This is a physical picture of the stone slab prepared in Example 2 of the present invention;
[0031] Figure 3 This is a physical picture of the stone slab prepared in Example 3 of the present invention;
[0032] Figure 4 This is a physical picture of the stone slab prepared in Example 4 of the present invention;
[0033] Figure 5 This is a physical picture of the stone slab prepared in Example 5 of the present invention;
[0034] Figure 6 This is a physical picture of the stone slab prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0036] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0037] Example 1
[0038] Prepare the raw materials according to the following ratio:
[0039] Unsaturated polyester resin liquid A 5%wt, unsaturated polyester resin liquid B 10%wt, mica flakes 40%wt and filler 45%wt;
[0040] The unsaturated polyester resin liquid A is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.1 parts of curing agent (methyl ethyl ketone oxide), 0.1 parts of accelerator (cobalt cyclohexaneate), 2 parts of coupling agent (γ-aminopropyl triethoxysilane), and 2 parts of inhibitor (stearic acid) and stirring them evenly.
[0041] Unsaturated polyester resin liquid B is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.5 parts of curing agent (methyl ethyl ketone oxide), 0.5 parts of accelerator (cobalt cyclohexane acid), 0.1 parts of coupling agent (γ-aminopropyl triethoxysilane), 0.1 parts of inhibitor (stearic acid), and 0.5 parts of color concentrate (metal complex dye) and stirring them evenly;
[0042] The filler is glass sand with a particle size of 0.061-30 mm.
[0043] Unsaturated polyester resin was purchased from Xinshuangli (Huizhou) Resin Co., Ltd., model 5088; epoxy resin was purchased from Dongguan Kress New Materials Co., Ltd., mica sheets with a side length of 5-400mm and a thickness of 0.01-30mm were purchased from Lingshou County Aochen Mineral Products Processing Factory; glass sand was purchased from Foshan Sanshui District Hongjia Glass Products Co., Ltd., quartz sand was purchased from Hezhou Xuxin Mineral Products Processing Co., Ltd., and the metal complex dye was a yellow dye purchased from Xingtai Pertu Dye Co., Ltd.
[0044] Follow the steps below to prepare artificial stone slabs:
[0045] S1, stir the unsaturated polyester resin liquid A evenly, pour it into the mold, solidify it, and form a transparent protective layer; the thickness of the protective layer is 1mm
[0046] S2, mixing the unsaturated polyester resin liquid B and the mica flakes, stirring evenly, pouring into a mold, and flattening and compacting;
[0047] S3, pouring the filler into the mold, pressing it with high-frequency vibration under a vacuum condition of -0.1MPa, and then transferring it to a curing furnace for curing and cooling to obtain a stone blank;
[0048] S4, a scraping machine scrapes and levels the stone blank;
[0049] S5, apply an unsaturated polyester resin layer on the surface of the transparent protective layer of the stone blank with a thickness of 1mm.
[0050] Curing and polishing are performed to obtain the artificial stone plate.
[0051] Example 2
[0052] Prepare the raw materials according to the following ratio:
[0053] Unsaturated polyester resin liquid A 10% wt, unsaturated polyester resin liquid B 15% wt, mica flakes 30% wt and filler 45% wt;
[0054] The unsaturated polyester resin liquid A is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.1 parts of curing agent (methyl ethyl ketone oxide), 0.1 parts of accelerator (cobalt cyclohexaneate), 2 parts of coupling agent (γ-aminopropyl triethoxysilane), and 2 parts of inhibitor (stearic acid) and stirring them evenly.
[0055] Unsaturated polyester resin liquid B is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.5 parts of curing agent (methyl ethyl ketone oxide), 0.5 parts of accelerator (cobalt cyclohexane acid), 0.1 parts of coupling agent (γ-aminopropyl triethoxysilane), 0.1 parts of inhibitor (stearic acid), and 0.5 parts of color concentrate (metal complex dye) and stirring them evenly;
[0056] The filler is glass sand with a particle size of 0.061-30 mm. The metal complex dye is a blue dye purchased from Xingtai Pertu Dye Co., Ltd.
[0057] Follow the steps below to prepare artificial stone slabs:
[0058] S1, stirring the unsaturated polyester resin liquid A evenly, pouring it into a mold, and curing it to form a transparent protective layer; the thickness of the protective layer is 1 mm.
[0059] S2, mixing the unsaturated polyester resin liquid B and the mica flakes, stirring evenly, pouring into a mold, and flattening and compacting;
[0060] S3, pouring the filler into the mold, pressing it with high-frequency vibration under a vacuum condition of -0.1MPa, and then transferring it to a curing furnace for curing and cooling to obtain a stone blank;
[0061] S4, a scraping machine scrapes and levels the stone blank;
[0062] S5, coating an unsaturated polyester resin layer with a thickness of 1 mm on the surface of the transparent protective layer of the stone blank, curing, and polishing to obtain the artificial stone plate.
[0063] Example 3
[0064] Prepare the raw materials according to the following ratio:
[0065] Unsaturated polyester resin liquid A 20%wt, unsaturated polyester resin liquid B 30%wt, mica flakes 30%wt and filler 20%wt;
[0066] The unsaturated polyester resin liquid A is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.1 parts of curing agent (methyl ethyl ketone oxide), 0.1 parts of accelerator (cobalt cyclohexaneate), 2 parts of coupling agent (γ-aminopropyl triethoxysilane), and 2 parts of inhibitor (stearic acid) and stirring them evenly.
[0067] Unsaturated polyester resin liquid B is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.5 parts of curing agent (methyl ethyl ketone oxide), 0.5 parts of accelerator (cobalt cyclohexaneate), 0.1 parts of coupling agent (γ-aminopropyl triethoxysilane), and 0.1 parts of inhibitor (stearic acid) and stirring them evenly;
[0068] The filler is glass sand with a particle size of 0.061-30 mm. The artificial stone slab is prepared according to the following steps:
[0069] S1, stir the unsaturated polyester resin liquid A evenly, pour it into the mold, solidify it, and form a transparent protective layer; the thickness of the protective layer is 3mm
[0070] S2, mixing the unsaturated polyester resin liquid B and the mica flakes, stirring evenly, pouring into a mold, and flattening and compacting;
[0071] S3, pouring the filler into the mold, pressing it with high-frequency vibration under a vacuum condition of -0.1MPa, and then transferring it to a curing furnace for curing and cooling to obtain a stone blank;
[0072] S4, a scraping machine scrapes and levels the stone blank;
[0073] S5, coating an unsaturated polyester resin layer with a thickness of 3 mm on the surface of the transparent protective layer of the stone blank, curing, and polishing to obtain the artificial stone plate.
[0074] Example 4
[0075] Prepare the raw materials according to the following ratio:
[0076] Unsaturated polyester resin liquid A 15%wt, unsaturated polyester resin liquid B 20%wt, mica flakes 20%wt and filler 60%wt;
[0077] The unsaturated polyester resin liquid A is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.1 parts of curing agent (methyl ethyl ketone oxide), 0.1 parts of accelerator (cobalt cyclohexaneate), 2 parts of coupling agent (γ-aminopropyl triethoxysilane), and 2 parts of inhibitor (stearic acid) and stirring them evenly.
[0078] Unsaturated polyester resin liquid B is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.5 parts of curing agent (methyl ethyl ketone oxide), 0.5 parts of accelerator (cobalt cyclohexane acid), 0.1 parts of coupling agent (γ-aminopropyl triethoxysilane), 0.1 parts of inhibitor (stearic acid), and 0.5 parts of color concentrate (metal complex dye) and stirring them evenly;
[0079] The filler is glass sand with a particle size of 0.061-30 mm. The metal complex dyes are yellow and blue dyes purchased from Xingtai Pertu Dye Co., Ltd.
[0080] Follow the steps below to prepare artificial stone slabs:
[0081] S1, stir the unsaturated polyester resin liquid A evenly, pour it into the mold, solidify it, and form a transparent protective layer; the thickness of the protective layer is 1mm
[0082] S2, mixing the unsaturated polyester resin liquid B and the mica flakes, stirring evenly, pouring into a mold, and flattening and compacting;
[0083] S3, pouring the filler into the mold, pressing it with high-frequency vibration under a vacuum condition of -0.1MPa, and then transferring it to a curing furnace for curing and cooling to obtain a stone blank;
[0084] S4, a scraping machine scrapes and levels the stone blank;
[0085] S5, coating an unsaturated polyester resin layer with a thickness of 1 mm on the surface of the transparent protective layer of the stone blank, curing, and polishing to obtain the artificial stone plate.
[0086] Example 5
[0087] Prepare the raw materials according to the following ratio:
[0088] Unsaturated polyester resin liquid A 15% wt, unsaturated polyester resin liquid B 15% wt, mica flakes 10% wt and filler 60% wt;
[0089] The unsaturated polyester resin liquid A is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.1 parts of curing agent (methyl ethyl ketone oxide), 0.1 parts of accelerator (cobalt cyclohexaneate), 2 parts of coupling agent (γ-aminopropyl triethoxysilane), and 2 parts of inhibitor (stearic acid) and stirring them evenly.
[0090] Unsaturated polyester resin liquid B is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.5 parts of curing agent (methyl ethyl ketone oxide), 0.5 parts of accelerator (cobalt cyclohexane acid), 0.1 parts of coupling agent (γ-aminopropyl triethoxysilane), 0.1 parts of inhibitor (stearic acid), and 0.5 parts of color concentrate (metal complex dye) and stirring them evenly;
[0091] The filler is glass sand with a particle size of 0.061-30 mm. The metal complex dye is a yellow dye purchased from Xingtai Pertu Dye Co., Ltd.
[0092] Follow the steps below to prepare artificial stone slabs:
[0093] S1, stir the unsaturated polyester resin liquid A evenly, pour it into the mold, solidify it, and form a transparent protective layer; the thickness of the protective layer is 1mm
[0094] S2, mixing the unsaturated polyester resin liquid B and the mica flakes, stirring evenly, pouring into a mold, and flattening and compacting;
[0095] S3, pouring the filler into the mold, pressing it with high-frequency vibration under a vacuum condition of -0.1MPa, and then transferring it to a curing furnace for curing and cooling to obtain a stone blank;
[0096] S4, a scraping machine scrapes and levels the stone blank;
[0097] S5, coating an unsaturated polyester resin layer with a thickness of 1 mm on the surface of the transparent protective layer of the stone blank, curing, and polishing to obtain the artificial stone plate.
[0098] Example 6
[0099] The difference from Example 1 is that in this embodiment:
[0100] Unsaturated polyester resin liquid A is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.5 parts of curing agent (methyl isobutyl ketone peroxide), 0.5 parts of accelerator (cobalt cyclohexaneate), 1 part of coupling agent (γ-aminopropyl triethoxysilane), and 1 part of inhibitor (stearic acid) and stirring them evenly;
[0101] Unsaturated polyester resin liquid B is prepared by mixing 100 parts by weight of unsaturated polyester resin, 0.5 parts of curing agent (methyl ethyl ketone oxide), 0.5 parts of accelerator (cobalt isooctanoate), 1 part of coupling agent (γ-aminopropyltriethoxysilane), 1 part of inhibitor (stearic acid), and 1 part of color essence (metal complex dye) and stirring evenly.
[0102] The metal complex dyes of the present embodiment are blue and yellow dyes purchased from Xingtai Pertu Dye Co., Ltd.
[0103] Example 7
[0104] The difference from Example 1 is that in this embodiment:
[0105] Unsaturated polyester resin liquid A is prepared by mixing 100 parts by weight of unsaturated polyester resin, 2 parts of curing agent (methyl ethyl ketone oxide), 2 parts of accelerator (N,N-dimethylaniline), 1 part of coupling agent (γ-aminopropyltriethoxysilane), and 1 part of polymerization inhibitor (dioctyl phthalate) and stirring them evenly;
[0106] Unsaturated polyester resin liquid B is prepared by mixing 100 parts by weight of unsaturated polyester resin, 2 parts of curing agent (methyl ethyl ketone oxide), 2 parts of accelerator (N,N-dimethylaniline), 1 part of coupling agent (γ-aminopropyltriethoxysilane), 1 part of inhibitor (dioctyl phthalate), and 1 part of color essence (metal complex dye) and stirring evenly.
[0107] Example 8
[0108] The difference from Example 1 is that in this embodiment:
[0109] Unsaturated polyester resin liquid A is prepared by mixing 100 parts by weight of unsaturated polyester resin, 1 part of curing agent (isopropylbenzene hydroperoxide), 1 part of accelerator (N,N-dimethylaniline), 2 parts of coupling agent (γ-aminopropyltriethoxysilane), and 2 parts of inhibitor (epoxy resin) and stirring them evenly;
[0110] Unsaturated polyester resin liquid B is prepared by mixing 100 parts by weight of unsaturated polyester resin, 2 parts of curing agent (isopropylbenzene hydroperoxide), 2 parts of accelerator (N,N-dimethylaniline), 2 parts of coupling agent (γ-aminopropyltriethoxysilane), 2 parts of inhibitor (epoxy resin), and 1 part of color essence (metal complex dye) and stirring evenly.
[0111] Comparative Example 1
[0112] The difference from Example 1 is that in step S2 of this comparative example, mica flakes are not added, and an equal amount of quartz sand is used instead of mica flakes, and the remaining raw materials and steps are the same as those of Example 1.
[0113] Comparative Example 2
[0114] The difference from Example 1 is that step S1 is not performed in this comparative example, the unsaturated polyester resin liquid A in step S1 of Example 1 is mixed with the unsaturated polyester resin liquid B and mica flakes in step S2, and the remaining raw materials and steps are the same as those of Example 1.
[0115] Experimental example
[0116] The stones of Examples 1-5 and Comparative Examples 1-2 were used as samples to test the glossiness of the stones and the appearance of the pipe stones. The results are shown in Table 1. The glossiness of the stones was measured by a DG60-Pro gloss meter from Hangzhou Caipu Technology Co., Ltd.
[0117] Table 1 Stone test results of 1-5 and comparative examples 1-2
[0118]
[0119] From Table 1 and Appendix Figure 1-6 It can be concluded that the stones of Examples 1-5 have high surface gloss, the texture of the mica flakes on the stone surface is clear, the layered texture on the stone surface can be observed by the naked eye, and the brightness and color that can be observed by the naked eye are rich, the texture is good, and it has a strong pearlescent effect, color effect and perspective color effect, which is different from the decorative effect of traditional artificial stone. The stone in Comparative Example 1 does not have mica flakes added, and its stone surface only has the texture of resin. Figure 1-5 and Figure 6 , it can be clearly seen that Figure 6 The stone surface in the example does not have pearlescent effect, color effect and perspective flash color effect. The stone in comparative example 2 does not have a transparent protective layer. When the stone is scraped and the thickness is determined, part of the mica flakes are exposed, and water enters between the layered structures of the mica, causing the surface of the stone to bulge locally in the later stage.
[0120] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. An artificial stone plate, characterized in that: Calculated by mass percentage, including the following raw materials: Unsaturated polyester resin liquid A 5-20%, unsaturated polyester resin liquid B 10-30%, mica flakes 1-40% and filler 20-60%; The unsaturated polyester resin liquid A comprises the following raw materials by weight: 100 parts of unsaturated polyester resin, 0.1-2 parts of curing agent, 0.1-2 parts of accelerator, 0.1-2 parts of coupling agent, and 0.1-2 parts of inhibitor; The unsaturated polyester resin liquid B comprises the following raw materials by weight: 100 parts of unsaturated polyester resin, 0.1-2 parts of curing agent, 0.1-2 parts of accelerator, 0.1-2 parts of coupling agent, 0.1-2 parts of inhibitor; and 0.01-1 parts of color concentrate.
2. The artificial stone plate according to claim 1, characterized in that: The filler is glass sand or quartz sand, and the particle size of the filler is 0.061-30 mm.
3. The artificial stone plate according to claim 1, characterized in that: The curing agent is one of methyl ethyl ketone peroxide, cyclohexanone peroxide, methyl isobutyl ketone peroxide, benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, 2,4-dichlorobenzoyl peroxide and dodecyl peroxide.
4. The artificial stone plate according to claim 1, characterized in that: The promoter is one of cobalt naphthenate, vanadium naphthenate, cobalt isooctanoate, vanadium isooctanoate and N,N-dimethylaniline.
5. The artificial stone plate according to claim 1, characterized in that: The polymerization inhibitor is one of stearic acid, epoxy resin and dioctyl phthalate.
6. The artificial stone plate according to claim 1, characterized in that: The coupling agent is a silane coupling agent or a titanate coupling agent.
7. A method for preparing an artificial stone plate according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, stirring the unsaturated polyester resin liquid A evenly, pouring it into a mold, and curing it to form a transparent protective layer; S2, mixing the unsaturated polyester resin liquid B and the mica flakes, stirring evenly, pouring into a mold, and flattening and compacting; S3, pouring the filler into the mold, vibrating and pressing under vacuum, solidifying and forming, and obtaining a stone blank; S4, a scraping machine scrapes and levels the stone blank; S5, coating a resin layer on the surface of the transparent protective layer of the stone blank, curing, and polishing to obtain the artificial stone plate.
8. The method for preparing an artificial stone plate according to claim 7, characterized in that: In the step S1, the transparent layer has a thickness of 1-5 mm.
9. The method for preparing an artificial stone plate according to claim 7, characterized in that: In the step S5, the thickness of the resin layer is 1-3 mm.
10. The method for preparing an artificial stone plate according to claim 7, characterized in that: In the step S5, the raw material of the resin layer is one of unsaturated polyester resin, epoxy resin and UV resin.
